Pengelolaan Hutan Adat Depati Karo Jayo Tuo Berbasis Kearifan Lokal di Desa Rantau Kermas Kecamatan Jangkat Kabupaten Merangin - Miranti, Miranti; Epriadi, Dedi (Universitas Muara Bungo, 2024)
Forests are the lungs of the earth where there are many animals living in them and there are also trees and various other types. Currently, forest management is carried out with the existence of customary forests that are managed, supervised and preserved by the surrounding community so that the customary forest can be maintained by making it a tourist attraction with existing local wisdom. The purpose of this study was to determine how the customary forest is managed as a tourist attraction and to determine the supporting and inhibiting factors in the management of customary forests in Rantau Kermas Village. The type of research used is a descriptive qualitative method used in examining the symptoms related to one another. The techniques used are data reduction, data presentation, verification and drawing conclusions and documentation. The results of this study are that customary forest management can be categorized as the use of forests as livelihood land, the use of forests as settlements and the protection of customary forests.